Variation in Pathologist Classification of Colorectal Adenomas and Serrated Polyps. (March 2018) - Gourevitch, Rebecca A; Rose, Sherri; Crockett, Seth D; Morris, Michele; Carrell, David S; Greer, Julia B; Pai, Reetesh K; Schoen, Robert E; Mehrotra, Ateev
Abstract : OBJECTIVES: Endoscopist quality measures such as adenoma detection rate (ADR) and serrated polyp detection rates (SPDRs) depend on pathologist classification of histology. Although variation in pathologic interpretation is recognized, we add to the literature by quantifying the impact of pathologic variability on endoscopist performance. METHODS: We used natural language processing to abstract relevant data from colonoscopy and related pathology reports performed over 2 years at four clinical sites. We quantified each pathologist's likelihood of classifying polyp specimens as adenomas or serrated polyps. We estimated the impact on endoscopists' ADR and SPDR of sending their specimens to pathologists with higher or lower classification rates. RESULTS: We observed 85, 526 colonoscopies performed by 119 endoscopists; 50, 453 had a polyp specimen, which were analyzed by 48 pathologists. There was greater variation across pathologists in classification of serrated polyps than in classification of adenomas. We estimate the endoscopist's average SPDR would be 0.5% if all their specimens were analyzed by the pathologist in our sample with the lowest classification rate and 12.0% if all their specimens were analyzed by the pathologist with the highest classification rate. In contrast, the endoscopist's average ADR would be 28.5% and 42.4% if their specimens were analyzed by the pathologist with lowest and highest classification rate, respectively. CONCLUSIONS: There is significant variation in pathologic interpretation, which more substantially affects endoscopist SPDR than ADR.